Implementation Of Good Manufacturing Practices (Gmp) In Marine Product Processing At Kampung Kelembak - Nuryanto, Heri (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
The aim of this community service activity in Kampung Kelembak is to improve students' skills and understanding through real experience in the community and provide solutions to the main problems of the Kampung Kelembak community through training in making shrimp dim sum. This community service activity is carried out using the Service Learning (SL) Methodology. From the implementation of the activity, the results were obtained: the participants were able to implement GMP shrimp dim sum; 100% of participants stated that this was their first time making shrimp dim sum; 83% of participants planned and expressed interest in producing shrimp dimsum for sale..